Cooperative Effect of GO and Glucose on PEDOT:PSS for High VOC and Hysteresis‐Free Solution‐Processed Perovskite Solar Cells. (22nd August 2016) - Giuri, Antonella; Masi, Sofia; Colella, Silvia; Kovtun, Alessandro; Dell'Elce, Simone; Treossi, Emanuele; Liscio, Andrea; Esposito Corcione, Carola; Rizzo, Aurora; Listorti, Andrea
Abstract : Hybrid organic–inorganic halide perovskites have emerged at the forefront of solution‐processable photovoltaic devices. Being the perovskite precursor mixture a complex equilibrium of species, it is very difficult to predict/control their interactions with different substrates, thus the final film properties and device performances. Here the wettability of CH3 NH3 PbI3 (MAPbI3 ) onto poly(3, 4‐ethylenedioxythiophene):poly(styrenesulfonate) (PEDOT:PSS) hole transporting layer is improved by exploiting the cooperative effect of graphene oxide (GO) and glucose inclusion. The glucose, in addition, triggers the reduction of GO, enhancing the conductivity of the PEDOT:PSS+GO+glucose based nanocomposite. The relevance of this approach toward photovoltaic applications is demonstrated by fabricating a hysteresis‐free MAPbI3 solar cells displaying a ≈37% improvement in power conversion efficiency if compared to a device grown onto pristine PEDOT:PSS. Most importantly, V OC reaches values over 1.05 V that are among the highest ever reported for PEDOT:PSS p‐i‐n device architecture, suggesting minimal recombination losses, high hole‐selectivity, and reduced trap density at the PEDOT:PSS along with optimized MAPbI3 coverage. Abstract : The synergistic effect of graphene oxide and glucose in improving the conduction properties of polymer electrolyte poly(3, 4‐ethylenedioxythiophene):poly(styrenesulfonate) and modifying the sensible interface of perovskite solar cells is reported. This method allows obtaining hysteresis‐free and high V OC CH3 NH3 PbI3 devices displaying a ≈37% improvement in power conversion efficiency, evidencing minimal recombination losses and very efficient charge extraction at the electrodes.